ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI IMPOR DAGING SAPI DI INDONESIA TAHUN 1995-2016 - Purba, Nadia Hosanna; Indrajaya, I Gst Bgs (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2020)
The purpose of this study is to analyze the effect of imported beef prices, local beef prices, consumption, and production on the volume of beef imports in Indonesia during the 1995-2016 period and to analyze the most dominant factors between import prices, local prices, consumption and production of beef imports in Indonesia. The data used in this study are secondary data with a period of 22 years, using double log multiple linear regression analysis techniques. The results show that simultaneously the price of imported beef, local beef prices, consumption and production have a significant effect on beef imports in Indonesia. Partially, import prices do not have a significant negative effect on beef imports in Indonesia, local prices and production have a negative effect on beef imports in Indonesia and consumption partially does not have a significant positive effect on beef imports in Indonesia. The dominant factor influencing the decline in beef imports in Indonesia is the production variable. Keywords : beef imports, import prices, local prices, consumption, production.